Chitin-Chitosan - Myriad Functionalities in Science and Technology 2018
DOI: 10.5772/intechopen.76037
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Electrospinned Chitosan Nanofiber Composites for Wound Dressings

Abstract: Chitosan has a medical application because of its natural origin and properties of biodegradability, biocompatibility, nontoxicity, and antimicrobial capacity. Electrospinning produces non-woven nanofibers to wound dressing with high specific surface area and small pores. These properties are favorable for absorption of exudates and prevent the penetration of bacteria, thus promoting wound healing. For this reason, chitosan blends are used to produce nanofiber dressings, and the characterization of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, the polycationic nature and rigid chemical structure of chitosan limits its electrospinnability. The formation of nanofibers is facilitated by blending chitosan with another polymer, thereby allowing the formation of hydrogen bonds (Cázarez et al, 2018). Chitosan has been combined with PEO, poly (lactic-co-glycolic acid) (PLGA), and polyacrylamide to form nanofibers, which have served as delivery systems, respectively, for Bacillus sp.…”
Section: Polymers Natural Polymersmentioning
confidence: 99%
“…Nevertheless, the polycationic nature and rigid chemical structure of chitosan limits its electrospinnability. The formation of nanofibers is facilitated by blending chitosan with another polymer, thereby allowing the formation of hydrogen bonds (Cázarez et al, 2018). Chitosan has been combined with PEO, poly (lactic-co-glycolic acid) (PLGA), and polyacrylamide to form nanofibers, which have served as delivery systems, respectively, for Bacillus sp.…”
Section: Polymers Natural Polymersmentioning
confidence: 99%
“…The specific antibacterial activitywas measured using half maximal inhibitory concentration technique starting from the usedconcentration to prepare the blends (4 mg/ml). Figure (8) showed that the inhibition halo around small drop of used solution on the surface of agar after spread of Escherichia coliand incubated at 37°C for 24 hours. The highest inhibition of the bacteria was for Chitosan/PEOblend prepared at90:10 ratios withinhibition halo of 13mm at 40mg/ml concentration and still effective to 1/32 of the initial concentration (1.25mg/ml) but with less efficiency of halo diameter of 6mm (Table 2).…”
Section: Figure (7): Young Modulus For Chitosan/peo Blend With Peo Ratiomentioning
confidence: 99%
“…In addition, Chitosan is used in different biomedical applications due to its natural origin, biodegradability, biocompatibility, nontoxicity and antimicrobial activity. It is used in preventing wound infections, drug delivery, drug encapsulation, wound dressing and scaffolds for bone and nerve regeneration [8] . Also, blends-based chitosan are used as antimicrobial substance in food packaging [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has a strong and unique antibiotic activity [19] . It has been used in the treatment of hypertension [20] , respiratory infections [21] , healing wound injuries, and ulcers [22] . C. molmol effectively treated protozoa [23,24] and helminths [25][26][27] infections.…”
Section: Introductionmentioning
confidence: 99%